The Relationship between Meaning in Life and Depression, Anxiety and Stress Status among College Students of Iran University of Medical Sciences In 2013 - Dehdari T; Yarahmadi R; Taghdisi MH; Daneshvar R; Ahmad Poor J (Iranian Association of Health Education and Health Promotion, 2013)
Background and objective: The reason behind many psychological problems is that there is no meaning in life. This study aimed to determine the relationship between meaning in life with depression, anxiety and stress status among college students of Iran University of Medical Sciences (IUMS) in 2013. Methods: In this descriptive-analytical study, 222 college students living in dormitories at IUMS completed a questionnaire consisting demographic characteristics, depression, anxiety, and stress and meaning in life scales. The collected data were analyzed by using SPSS18 through the independent-samples t, Pearson correlation and One-way ANOVA tests. Results: The mean age of the participants was 23 (±3.6) years. 50.5% of students had some degrees of depression 30.9% had some degrees of stress, and 73% had anxiety to some degree (mild to extremely severe). The results showed that the average score of anxiety was significantly related to meaning in life (p=0.04). Also, there were significant associations between the mean scores of depression, anxiety and stress among students (p>0.05). Conclusion: Meaning in life is a factor influencing the college students, anxiety. In the psychological counseling, logotherapy methods can improve the meaning in life and mental health of college students.